Da prosa marginal à literatura underground de Lourenço Mutarelli: O Cheiro do Ralo - Silva, Damásio Marques da (2014)
The main objective of this thesis is the analysis of O Cheiro do Ralo (2002), the debut novel by the cartoonist Lourenço Mutarelli. The purpose is to understand the underground language in the hybrid structure within the form of the romance genre. We have made a discursive structural comparison between O Cheiro do Ralo and Rabelais's work, Gargantua (1985) and O terceiro livro dos fatos e ditos heróicos do bom Pantagruel (2006). We associate the marginal language represented by Mutarelli with the works of artists such as Renoir, Munch and Bosch, besides the musical art. All of them are understood as reading devices of the novel, and support the references or the appropriations made by the author in the process of framing the narrative. The contamination of these languages one each other is made by the voice of the implicit narrator. In addition, the selected theories of Bakhtin about plurilingualism and skaz support the research from the social discourse standpoint, and the critical work of Will Eisner (2010; 2013) sustains the entry of the author's voice through the current artwork, mainly, in the language of the graphic novel. It is the entrance of the language of comics, which allows the introduction of these artistic languages contained within the production of Mutarelli before his debut novel. The hypotheses assert that O Cheiro do Ralo is located at the threshold of the novel and the graphic novel, by transiting between the two genres without fixating on any of them. Whereas the underground language differs from the marginal language through certain artistic procedures, and through the recycling of other languages, such as the grotesque and the language of the streets. It is concluded that O Cheiro do Ralo stands as a mediating work of inclusion of the underground literature supported by the marginal one, which is, in turn, evidenced by the artistic imaginary. The cartoonist converges toward to the contemporary scripture in an original language that tells and shows as image and social voice in the Underground Literature